Structured and interactive improvisation scenarios (2021)
The musical improvisation system VMO-Score has been proposed to mitigate the problems of lack of fluidity in the musical result and use of static improvisation scenarios present in the current mechanisms of musical improvisation. VMO-Score has been successfully tested by different artists, but its use is completely dependent on Max/MSP. This software is private and only works on Windows and OS X operating systems, so the use of VMO-Score is limited to a small audience. The objective of this project is to develop the core components of the VMO-Score system as plugins for the ossia-score sequencer to provide musicians with a completely open-source, multiplatform, ergonomic and independent music improvisation platform allowing (1) the construction of interactive scenarios; (2) the generation of guided transitions; and (3) the interaction between the performers or the environment with the system during improvisation.